Improving Software Development Processes : Transition from SVN to GIT - Biastinova, Aiyyna; Bruckner, Tomáš, 1974-; Vorlíček, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
In recent years, IT organizations have migrated from Subversion (SVN), a centralized version control system, to the distributed Git platform. Surveys show that 93.87 \% of professional developers use Git in their daily workflows. Large enterprises with massive legacy codebases and complex product portfolios often face significant technical and organizational challenges when migrating from SVN to Git. This thesis first conducted a workflow analysis of an organization that relied on SVN to identify common pain points. Based on these findings, a generic, step-by-step migration guide for moving repositories to the Git platform was developed. To validate its practicality, the guide was applied in a sandbox environment. The final validation confirmed that the proposed guide reliably minimizes migration risks and equips large development teams for a seamless transition to Git. In addition, adopting Git's distributed and feature-branching workflows transforms the software delivery lifecycle, resulting in measurable improvements in code quality and product delivery.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: business analýza [obor dipl. práce]; diplomové práce; master's theses